Through the Optics of Finance: Speculative Urbanism and the Transformation of Markets - Goldman, Michael; Narayan, Devika (International journal of urban and regional research, 2021)
This article contributes to debates on the financialization of global South economies by looking closely at how India's real estate markets became entwined with global financial networks. We offer an analytical frame that centers on the strategies of global finance and its ability to transform its form and mode of operation when faced with a supposed ‘limit’, both spatially and temporally. Finance capital, we argue, derives its power from working with state actors and ambitious borrowers—across borders, sectors and conditions—to spawn new investment opportunities and, over time, a financialized type of urban transformation. In 2005, India deregulated foreign investment into land and real estate, a watershed moment that radically altered the financial and urban speculative logics of the sector. Private equity firms made vast investments into urban projects, anticipating massive returns, and even though the bubble quickly burst, India continues to attract finance capital. We explain this conundrum by tracking the new techniques and investment tools of private equity (‘following the financial strategy’), arguing for an analytical approach attuned to the relentless dynamism and hyper‐mobility of finance capital (an ‘inter‐scalar and conjunctural dynamics approach’).